PENDIDIKAN KARAKTER MENUJU REVOLUSI MENTAL TERHADAP SUMBER DAYA MANUSIA MAHASISWA STIKES KARSA HUSADA GARUT - Andhika Lungguh Perceka; Herlin Rusyani; N. Ai Erlinawati; Novie Melliasany; Taufik Huda (LP4M STIKes Karsa Husada Garut, 2021)
As an Educational Institution at the Higher Education level, STIKes KHG has determined that the color and character of the science to be developed is based on